MOVEMENT TO EAT MACKEREL TO OVERCOME STUNTING IN CIOMAS DISTRIC BOGOR REGENCY - Indrayani, Triana; Wiranti, Ajeng Ratna; Aisya, Syifa Ayu; Silalahi, Lusia Desy Septiyana; Putri, Lioni Amelianti; Sonia, Sonia; Minangkabau, Siti Mawaddah (International Journal of Engagement and Empowerment (IJE2), 2025)
Stunting is a condition of impaired growth and development in children under five due to chronic malnutrition, resulting in a child being too short for their age. Nutritional deficiencies begin during pregnancy and in the early postnatal period; however, the signs of stunting typically become apparent after the child reaches two years of age. Stunting has a significant impact on the quality of human resources. In the short term, it affects brain development, intelligence, physical growth, and metabolism. In the long term, it leads to decreased cognitive abilities, weakened immune function, increased risk of metabolic diseases, and learning difficulties. Stunting prevention is currently one of the government's main priorities. In addition to education about stunting, another preventive measure is the optimization of animal protein intake, such as through the consumption of mackerel. Mackerel is a locally available, highly nutritious fish. This community service program aims to raise public awareness about the importance of animal protein consumption in the prevention of stunting. With improved understanding, it is expected that communities will be able to meet daily protein needs, especially for infants and young children. To raise awareness and promote behavioral change in the community, particularly in fostering the habit of consuming animal-based protein as a strategy to prevent stunting. The intervention involved educational sessions about stunting, the introduction of the “Gemakan Kemuning” campaign an initiative promoting mackerel consumption to combat stunting, video demonstrations on mackerel-based food preparation, and the distribution of mackerel-based food products. The activity was conducted on Thursday, June 12, 2025, at community health centre Kemuning 3, Bogor Regency, and was attended by 35 mothers with infants or toddlers. The program encompassed preparation, implementation, and evaluation phases. Educational content included definitions, causes, symptoms, impacts, prevention, and management of stunting. The program was successfully implemented. It is recommended that similar initiatives be continued and expanded by other healthcare professionals so that communities can better understand how to prevent and manage stunting, including by increasing their consumption of animal protein sources such as mackerel.